2007
DOI: 10.1080/13625180701393611
|View full text |Cite
|
Sign up to set email alerts
|

Transverse limb reduction and intrauterine device: Case report and review of the literature

Abstract: We present a rare case of transverse limb reduction defect associated with the presence of an IUD at the time of conception. The device had been removed in the first trimester of the pregnancy. Data from the literature are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Many women terminate the pregnancy on conception with an IUD; however, there have been reports of term pregnancies with an IUD still in situ. Although there are a few case reports of limb reduction defects in pregnancies where a woman had a Cu IUD in place [200], large‐scale studies have concluded that the Cu IUD does not increase the incidence of developmental defects [201]. Consistent with the human data, in experimental studies, exposing multiple species of embryos to Cu IUD has not been reported to result in direct teratogenic effects with respect to gross malformations, although modest reductions in growth have been noted [202, 203].…”
Section: Copper Toxicity and Developmental Outcomesmentioning
confidence: 99%
“…Many women terminate the pregnancy on conception with an IUD; however, there have been reports of term pregnancies with an IUD still in situ. Although there are a few case reports of limb reduction defects in pregnancies where a woman had a Cu IUD in place [200], large‐scale studies have concluded that the Cu IUD does not increase the incidence of developmental defects [201]. Consistent with the human data, in experimental studies, exposing multiple species of embryos to Cu IUD has not been reported to result in direct teratogenic effects with respect to gross malformations, although modest reductions in growth have been noted [202, 203].…”
Section: Copper Toxicity and Developmental Outcomesmentioning
confidence: 99%
“…Transverse limb defects were also found to be associated with low intake of dietary riboflavin 17. The use of an intrauterine contraceptive device has also been implicated in a case of transverse limb reduction defect 18…”
Section: Discussionmentioning
confidence: 99%